Development of strategies for enhancing cybersecurity and digital trust in Azerbaijan’s digital landscape - Alasgarova, Khayala; Ramazanov, Sahib (Technology audit and production reserves, 2025)
This research focuses on assessing cybersecurity practices and the level of digital trust in Azerbaijan and identifying key weaknesses using real-world data. The object of the research is cybersecurity practices and digital trust among organizations and users in Azerbaijan. The research solves the problem of insufficient empirical data on cybersecurity practices and digital trust in Azerbaijan, which contributes to low awareness, weak security implementation, frequent cyber incidents, and limited trust in digital services and legislation. The research methodology included a quantitative survey of 129 participants, Spearman correlation analysis, and risk heatmap modeling. Data analysis was conducted using a personal computer with Microsoft Excel and (Statistical Package for the Social Sciences) SPSS software. The results show that 55% of organizations have moderate cybersecurity awareness, 17.8% have low awareness, and 53.5% do not provide cybersecurity training to employees. Although 76% of banks use multifactor authentication (MFA), 40.3% have experienced fraud incidents. Spearman correlation analysis indicates a negative relationship between awareness and cyber incidents (–0.33) and between training and incidents (–0.29), while MFA usage shows a positive correlation with fraud detection (+0.3446). In addition, 64.3% of users feel somewhat safe, and 41.1% identify public education as the most important area requiring improvement. The findings demonstrate that insufficient training, incomplete adoption of modern protective measures, and weak public education increase cybersecurity risks even in organizations with moderate awareness. The results can support the State Service for Special Communication and Information Security (SSSCIS) in improving the National Cybersecurity Strategy and assist banks, businesses, and educational institutions in strengthening cybersecurity practices for the period 2025–2030.